Purification religious transformations of body and mind - Martin, Gerhard Marcel 1942-; Triplett, Katja 1968- (Bloomsbury, 2013)
In the religions of the world, there is strong emphasis on the practice of ""purification"" for the religious transformation of mind and body in connection with achieving such ultimate objectives as enlightenment and salvation. The contributors discuss the great diversity of forms and meanings with respect to religious transformation in their respective fields of research. While invoking earlier debates within the study of religions and theology on the topic of ""purification"" the studies in this volume penetrate further into the meaning and structure of religious transformation of mind and b